2021
DOI: 10.4103/1735-5362.310521
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the effect of hydroalcoholic and flavonoid-enriched extracts of Dracocephalum kotschyi on indomethacin-induced gastric ulcer in rats

Abstract: Background and purpose: Dracocephalum kotschyi ( Zaringiah ) is a fragrant wild medicinal plant found in Iran. Traditionally, it is used for the treatment of rheumatism, asthma, and gastrointestinal ailments. So far no investigation has been done on the beneficial or side effects of D. kotschyi on peptic ulcer. Therefore, this research was performed to find out whether D. kotschyi extract would induce p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…15 Because of its inhibitory effect on prostaglandin synthesis, it can harm stomach tissue by increasing gastric acid and pepsin activity and lipid peroxidation and oxidative stress by generating free radicals like (MDA, and MPO). 16 In this study the sites where diclofenac sodium-induced gastric mucosal lesions were the glandular portion of the rat's stomach. The macroscopic appearance of these mucosal lesions is in accordance with the finding, in which they expressed a very similar gastric mucosal damage with close features for this current study.…”
Section: Discussionmentioning
confidence: 91%
“…15 Because of its inhibitory effect on prostaglandin synthesis, it can harm stomach tissue by increasing gastric acid and pepsin activity and lipid peroxidation and oxidative stress by generating free radicals like (MDA, and MPO). 16 In this study the sites where diclofenac sodium-induced gastric mucosal lesions were the glandular portion of the rat's stomach. The macroscopic appearance of these mucosal lesions is in accordance with the finding, in which they expressed a very similar gastric mucosal damage with close features for this current study.…”
Section: Discussionmentioning
confidence: 91%
“…Zaringiah is an Iranian herbal plant that is commercially cultivated for herbal medicinal utilization. Pharmacological investigations have revealed that in comparison with the other recognized herbal medicines possessing antispasmodic activity, D. kotschyi extract has a higher potency, efficacy, and relative selectivity (8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Therefore, it was selected as suitable candidate or further pharmacological evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the hydroalcoholic extract of D. kotschyi has been shown to inhibit ileum contractions both in vitro and in vivo situations (8)(9)(10)(11). In addition, it has anti-inflammatory effects on the stomach ulcer and induced colitis in animal models (15,16). Furthermore, D. kotschyi extract inhibits bronchial smooth muscle contractions and has shown both anti-inflammatory and anti-fibrotic properties in bleomycin induced bronchitis (12,14).…”
Section: Introductionmentioning
confidence: 99%
“…MN method proceeded according to the previously described procedure ( 6 ). The mice fasted for 4 h before the experiment and were treated as follows (6 mice in each group): ( 1 ) Control group, mice received a single i.p injection of normal saline and cosolvent (tween 2%); ( 2 3 4 ) indomethacin treatment groups, mice received a single i.p dose of indomethacin at 10, 20, and 40 mg/kg ( 17 ); ( 5 6 7 ) indomethacin-curcumin treatment groups, mice received a single i.p dose of curcumin at 100 mg/kg ( 18 ) 30 min before a single i.p dose of indomethacin 10, 20, and 40 mg/kg.…”
Section: Methodsmentioning
confidence: 99%
“…Neutrophils can play a role in wound formation through the release of tissue-damaging proteases and reactive oxygen metabolites. This process is important in the pathogenesis of gastric ulcers process ( 7 ). Moreover, indomethacin can cause ROS production, and ROS formation plays an important role in the specific and idiosyncratic toxicity of indomethacin, such as bone marrow toxicity or liver inflammation ( 8 ).…”
Section: Introductionmentioning
confidence: 99%